DEVELOPMENT OF SODIUM SILICATE FREE BASED GEOPOLYMERS FOR UREA DIFFUSION STUDIES - ABDUL RAHIM, ROSNIZA HANIM (2015)
Geopolymers are inorganic polymers producedby alkali activationof materials rich in silica (Si) and alumina (Al).Limitedstudies has been done in synthesizing geopolymers without the use of sodium silicate solution. The objective of this work is to synthesise and evaluate the properties of geopolymers without using sodium silicate solution by varying Si/Al ratio using rice husk ash (RHA), sodium hydroxide (NaOH) concentration and solid/liquid ratio on the setting time, compressive strength, bulk porosity and density at different curing conditions for potential applications as a material for coating urea. The samples were prepared using fly ash and rice husk ash (RHA) and activatedusingNaOH. Further analysis of the geopolymers was also done using FESEM,XRD and FTIR. Correlation analysis between the synthesis parameters and the bulk porosity of geopolymers was done using multiple regression analysis.